(untitled) (Bangladesh Journal of Medical Science, 2021)
Background : Deletions in the β-globin gene cluster are usually rare, problematic to detect, and subsequently possess a challenge in many diagnostic laboratories. They are normally related to the heterozygous of the delta beta (δβ) thalassemia, hereditary persistence of fetalhemoglobin (HPFH) and some of the hemoglobin variants. These disorders are typically presented by elevated levels of hemoglobin F (Hb F), but with low to normal hemoglobin A2 (Hb A2). However, despite their existence, there is still a limited number of studies focusing on this area, hence no definitive diagnosis could be conclusively established. Therefore, this pilot study was carried out to fill this knowledge gap. Methods: In this study, screening of the selected deletional mutations in the β-globin gene cluster among patients with Hb F (>1%) and Hb A2 (<4%) were performed using multiplex Gap-PCR and multiplex ligation-dependent probe amplification (MLPA). Results: The results showed that out of 54 samples tested using multiplex Gap-PCR against four target deletions; Thai (δβ)°-thalassemia, HPFH-6, Siriraj J and HbLepore, one sample was found positive with Thai (δβ)°-thalassemia. Further findings from the MLPA screening on 12 randomly selected samples revealed that another patient was positive with double deletions within the region of the β-globin gene cluster. These deletions occur at the gamma-globin gene 1 (HBG1) and gamma-globin gene 2 (HBG2) in exon 3. Conclusions: In conclusion, this study highlighted the importance of these deletions’ characterization using multiplex Gap-PCR and MLPA which helps in establishing a definitive diagnosis among this selected group of patients. Bangladesh Journal of Medical Science Vol.20(3) 2021 p.618-624